2014
DOI: 10.6007/ijarbss/v4-i7/1032
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Food Quality Dimensions (Physical Environment, Food and Services) on Mental Image of the Restaurant and Customers' Satisfaction and Intentions based on Kisang's Model

Abstract: The present paper explores the effect of food quality dimensions (physical environment, food, and services) on mental image of the restaurant and customers' satisfaction and intentions based on Kisang's model (2012). In order to test the hypotheses, Kisang's questionnaire was used whose validity was measured via face validity and reliability was evaluated by means of Cronbach's alpha coefficient. The statistical sample included 208 customers of restaurants in Isfahan province who were selected via simple sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
2
0
6
Order By: Relevance
“…Finally, the outcomes of this study showed that physical environment has a significant positive impact on customer satisfaction, and were supported by past researches (Gagić et al, 2013;Haery & Badiezadeh, 2014;Nam et al, 2011;Ryu et al, 2012). Haider et al (2010) also found that physical environment was a key driver of brand preference.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, the outcomes of this study showed that physical environment has a significant positive impact on customer satisfaction, and were supported by past researches (Gagić et al, 2013;Haery & Badiezadeh, 2014;Nam et al, 2011;Ryu et al, 2012). Haider et al (2010) also found that physical environment was a key driver of brand preference.…”
Section: Discussionsupporting
confidence: 66%
“…Salah satu hal yang perlu diperhatikan terkait peningkatan kepuasan layanan adalah memperhatikan apa yang menjadi perhatian para pelanggan sehingga mereka tertarik untuk datang makan di restoran . Beberapa penelitian terkait menegaskan hal yang sama bahwa untuk menarik pehatian pelanggan untuk datang makan di restoran harus memperhatikan faktor-faktor terkait minat pelanggan seperti kualitas makanan dan kualitas layanan (Josiam, Molave, & Foster, 2014;Haery, 2014), suasana (Ryu & Jang, 2008), kewajaran harga (Ryu & Han, 2010), serta kenyamanan (Raab, Zemke, Hertzman, & Siggh, 2013).…”
Section: Pendahuluanunclassified
“…Beberapa penelitian juga mendapati faktor-faktor yang bisa membentuk kualitas layanan diantaranya: keramahan dan penampilan pegawai (Kim et al, 2009), ketrampilan di dalam penyajian makanan serta pengetahun mendalam tentang makanan yang disajikan (Markovic, Raspor, & Dorcic, 2011). Penelitian-penelitan terdahulu mendapati pentingnya faktor-faktor layanan dalam penilaian pelanggan (Ha & Jang, 2010;Ryu, Lee, & Kim, 2012;Haery, 2014;Jeong, Chun, Joo, & Yoon, 2013).…”
Section: Tinjauan Literaturunclassified
“…Dimensi kualitas (kualitas lingkungan fisik, kualitasmakanan, dan kualitas layanan) memiliki efekpositif dan signifikan terhadap citra mental pelanggandan berkaitan dengan restoran dan nilai yang dirasakan pelanggan. Efek dari gambaran mental pelanggan pada nilai yang dirasakan adalah positif dan signifikan ( Haery, 2014). Dalam bisnis restoran, pelanggan yang puasakan kembali dan memberikan word of mouth.…”
Section: Pustaka Ekuitas Pelangganunclassified